DTB Select: 4 | April 2017. Issue 4 (3rd April 2017) - Unknown
Abstract : Renal function monitoring of ACE inhibitors/AIIRAs ● Combating falsified medicines ● NHS England issues guidelines on conflicts of interest ● C difficile control interventions and fluoroquinolone prescribing ● NHS Scotland booklet for young people with autism ● Accuracy of asthma diagnosis in adults ● Continuity of care and reduced hospital admissions ● Screen and treat approaches for diabetes prevention